Toxicological And Psychosocial Impact Of Addictive Substances On Organ Function In Critical Cases And Challenges Of Care For Addicts In Intensive Care Units (The Review of Diabetic Studies, 2025)
Background and aim: Opioids pose a substantial issue, although there remains considerable ongoing utilization of formerly discredited substances. Addiction includes multiple problems that hinder patient movement and triage. Ingestion of atypical toxins might result in critical emergencies, necessitating differential diagnosis to avert organ injury. This research examines patients with a significant incidence of substance use, seeking to determine predictors of 30-day readmission.Materials and methods:• This prospective, observational cohort study investigated patients with substance use disorders (SUDs) admitted to the Intensive Care Unit (ICU) of Al-Azhar University hospitas. The study encompassed 50 adult patients (≥18 years) with confirmed or presumed substance use disorders (SUDs), employing a standardized data collection instrument derived from electronic health records and interviews. Essential data included demographics, causes for ICU admission, therapies, toxicological results, and psychosocial aspects. Statistical analyses, encompassing both univariate and multivariate techniques, were employed to ascertain risk factors associated with in-hospital mortality. Ethical approval was secured, accompanied by measures to guarantee informed consent from participants. The research sought to elucidate the obstacles in care and their effects on patient outcomes.Results A study including 50 middle-aged ICU patients with significant substance use revealed moderate to high severity (APACHE II 22.4, SOFA 8.7), with 56% displaying withdrawal symptoms and a 30-day readmission rate of 44%. Notable clinical findings included a high incidence of overdose admissions (30%) and affirmative urine screenings (40%). Significant connections existed between hepatic and renal failure and withdrawal symptoms, associated with prolonged ventilation (average duration of 45.6 hours) and extended hospitalizations.ConclusionThe study underscores the complex interaction between substance use disorders, mental health conditions, and increased readmission risks in ICU patients.